Channel pattern of proglacial rivers: topographic forcing due to glacier retreat - Marren, Philip M.; Toomath, Shamus C. (Earth Surface Processes and Landforms, 2016)
This is the peer reviewed version of the following article: Marren, P. M., & Toomath, S. C. (2014). Channel pattern of proglacial rivers: topographic forcing due to glacier retreat. Earth Surface Processes and Landforms, 39(7), 943–951. DOI:10.1002/esp.3545, which has been published in final form at http://onlinelibrary.wiley.com/doi/10.1002/esp.3545/abstract. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Self-Archiving Glacier retreat leads to changes in channel pattern during deglaciation, in response to changing water, sediment and base level controls. Recent ongoing retreat at Skaftafellsjökull, Iceland (c. 50m per year since 1998) has resulted in the formation of a sequence of river terraces, and several changes in river channel pattern. This paper compares widely used models of river channel pattern against the changes observed at Skaftafellsjökull. Doing this reveals the role of topographic forcing in determining proglacial channel pattern, whilst examining the predictive power and limitations of the various approaches to classifying river channels. Topography was found to play a large role in determining channel pattern in proglacial environments for two reasons: firstly, glacier retreat forces rivers to flow through confined moraine reaches. In these reaches, channels which theory predicts should be braided are forced to adopt a single channel. Secondly, proximal incision of proglacial rivers, accompanied by downstream aggradation, leads to changes in slope which force the river to cross channel pattern thresholds. The findings of this work indicate that in the short term, the majority of channel pattern change in proglacial rivers is due to topographic forcing, and that changes due to changing hydrology and sediment supply are initially relatively minor, although likely to increase in significance as deglaciation progresses. These findings have implications for palaeohydraulic studies, where changes in proglacial channel pattern are frequently interpretedas being due to changes in water or sediment supply. This paper shows that channel pattern can change at timescales faster than hydrological or sediment budget changes usually occur, in association with relatively minor changes in glacier mass balance.